Comparison of airborne bacterial communities in PM2.5 between a dry-season haze period and a wet-season non-haze period in thailand - Nopadol Precha; Kittipong Chaisiri; Suwalee Worakhunpiset; Yanin Limpanont; Naomichi Yamamoto; Wantanasak Suksong; Wissanupong Kliengchuay; Kraichat Tantrakarnapa (Scientific Reports)
Abstract Thailand experiencing severe air pollution for over a decade. Although the physical and chemical properties of particulate matter have been extensively studied, the biological aspects, particularly microorganisms present in fine particles during haze and non-haze periods, are still unclear. To address this gap, we aim to profile the bacterial communities in PM2.5 in Bangkok and Chiang Mai, Thailand. The samples were collected during the haze and non-haze periods in 2021–2022. Using 16 S rRNA gene sequencing, we identified a markedly higher number of bacterial genera in Chiang Mai (247) compared to Bangkok (31). In Bangkok, Actinobacteriota (80.4%) and Proteobacteria (18.3%) dominated, whereas Chiang Mai’s samples were enriched with Firmicutes (52.2%) and Bacteroidota (13.0%). Interestingly, Bangkok’s samples were dominated by Cutibacterium (68.4%) and Enhydrobacter (14.6%), while Chiang Mai had Bacillus (11.0%) and Blautia (7.6%). Despite substantially higher PM2.5 levels during haze, alpha diversity analyses showed that bacterial community structure was more strongly influenced by geographic location than by haze conditions. Chiang Mai consistently exhibited greater microbial richness and evenness than Bangkok. These findings highlight the importance of biological factors in urban air pollution studies and underscore the need to incorporate the biological aspects into health risk assessments and air quality management strategies.